Analisis Pengeluaran Pemerintah Di Sektor Kesehatan, Pendidikan, Dan Infrastruktur Terhadap Tingkat Kemiskinan Di Indonesia - Agustri Yogi Hidayat; Zul Azhar (Jurnal Kajian Ekonomi dan Pembangunan, 2022)
This study aims to determine: (1) the effect of government spending on the health sector on poverty in Indonesia, (2) the effect of government spending on the education sector on poverty in Indonesia, (3) the effect of government spending on the infrastructure sector on poverty in Indonesia. The type of research used is descriptive and associative. The data used in this study are secondary data from 2017 to 2019 in Indonesia using panel data with the random effect model approach. By doing analisis regression with random effect model, hypothesis test, and classical assumption test.The results of this study indicate that government spending in the health sector has a negative and insignificant effect on poverty in Indonesia with a probability of 0.9476. Index. Government spending in the education sector has a significant negative effect on poverty in Indonesia with a probability of 0.0030. Government spending in the infrastructure sector has a positive and insignificant effect on poverty in Indonesia with a probability of 0.5756 index.